Helmut Lachenmann: Das Mädchen mit den Schwefelhölzern - Lachenmann, Helmut 1935-; Zagrosek, Lothar; Staatsoper Stuttgart (Germany) (Wien KAIROS, 2002)
HELMUT LACHENMANN Das Maedchen mit den SchwefelhoelzernElizabeth Keusch soprano / Sarah Leonard sopranoSalome Kammer speaker / Mayumi Miyata shôYukiko Sugawara piano / Tomoko Hemmi pianoStaatsoper Stuttgart / Lothar Zagrosek conductorIncludes booklet with text by Helmut Lachenmann0012282KAI - 2001 - 2CD tracklisting:CD 1(01) Nr. 1 Auf der Straße (Oh du fröhliche) 7:12(02) Nr. 2 In dieser Kälte 1:56(03) Nr. 3 Frier-Arie 3:53(04) Nr. 4 Trio und Reprise 3:11 (Frier-Arie 2.Teil)(05) Nr. 5 Scherzo (Königin der Nacht) 2:38(06) Nr. 6 Schnalz-Arie Stille Nacht 3:06(07) Nr. 7 Zwei Wagen 0:52(08) Nr. 8 Die Jagd 3:51(09) Nr. 9 Schneeflocken 4:19(10) Nr. 10 Aus allen Fenstern 10:37(11) Nr. 11 Hauswand 1 9:05(12) Nr. 12 Ritsch 1 (Ofen) 3:55(13) Nr. 13 Hauswand 2 1:00 (Nr. 14 / Ritsch 2 gedeckter Tisch/Hauswand 3 - not applicable)(14) Nr. 15 Litanei 7:11CD 2(01) Nr. 16a Ritsch 3 0:28(02) Nr. 16b Kaufladen 3:41(03) Nr. 17 Abendsegen 4:10(04) Nr. 18 "...zwei Gefühle..." 22:29 Musik mit Leonardo(05) Nr. 19 Hauswand 4 2:34(06) Nr. 20a Ritsch 4 0:56(07) Nr. 20b Großmutter 1:25(08) Nr. 21 Nimm mich mit 2:57(09) Nr. 22 Himmelfahrt 2:58(10) Nr. 23 Shô 10:00(11) Nr. 24 Epilog 6:12TT: 2:00:52The event: Helmut Lachenmann's extraordinary music theatre, in a new production by the Stuttgart Opera, performed in Paris, is available here for the first time on CD. The precursor: Hans Christian Andersen's fairy tale. The little girl, who freezes to death on New Year's Eve, experiences a brief moment of happiness, as she dies, thanks to the matches....the sweet wretchedness is transposed into the existential sphere, but also into contemporary history. Texts by the German terrorist Gudrun Ensslin ensure that. The music is marked by intense physicality and sensuality.